2022
DOI: 10.1001/jamanetworkopen.2021.46175
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Common Infectious Diseases After COVID-19 Vaccination and Easing of Pandemic Restrictions in Israel

Abstract: IMPORTANCE Social restrictions intended to limit the transmission of SARS-CoV-2 may have also been associated with decreased rates of other communicable diseases. Evidence suggests that infection incidence rates (IRs) are rebounding after easing of social restrictions (eg, mask mandates).The reemergence of infectious disease complicates efforts to manage the ongoing COVID-19 pandemic. OBJECTIVETo examine IRs of frequently occurring infectious diseases after a successful SARS-CoV-2 vaccination campaign in Israe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 31 publications
5
37
1
Order By: Relevance
“…Utilizing the Pediatric Health Information System® (PHIS) database, an established collection of diagnoses associated with 51 children's hospitals, we found that the mean proportion of OM cases per 100 hospital visits and myringotomy tube placements decreased substantially at the beginning of the pandemic, which then rebounded by summer of 2021 [10] . These results follow loosely the conclusions of a recent paper from Israel, which suggested that shortly after social distancing mandates were lifted, there was an increase in non-Covid-19 related infectious diseases [11] . Further, Australia also performed an analysis which also reported increased RSV diagnoses after public health directives were reduced in the wake of a downtrend of Covid-19 cases [12] .…”
Section: Introductionsupporting
confidence: 90%
“…Utilizing the Pediatric Health Information System® (PHIS) database, an established collection of diagnoses associated with 51 children's hospitals, we found that the mean proportion of OM cases per 100 hospital visits and myringotomy tube placements decreased substantially at the beginning of the pandemic, which then rebounded by summer of 2021 [10] . These results follow loosely the conclusions of a recent paper from Israel, which suggested that shortly after social distancing mandates were lifted, there was an increase in non-Covid-19 related infectious diseases [11] . Further, Australia also performed an analysis which also reported increased RSV diagnoses after public health directives were reduced in the wake of a downtrend of Covid-19 cases [12] .…”
Section: Introductionsupporting
confidence: 90%
“…The high rate of RSV detection coincided with the surge in RSV infections identified in South Africa after the COVID-19 pandemic peak when lockdown measures were lifted [28] . This is in keeping with studies reporting a reduction of non-SARS-CoV-2 seasonal illnesses during periods of strict social restrictions as part of non-pharmaceutical interventions against COVID-19 [ 29 , 30 ] followed by an increased prevalence once social restrictions are eased [31] , [32] , [33] , [34] , [35] . This further highlights how difficult it is to distinguish children with SARS-CoV-2 infection from infection with other common respiratory viruses with the additional changes in patterns of non-SARS-CoV-2 infection transmission brought on by lockdown measures.…”
Section: Discussionsupporting
confidence: 87%
“…During this period, at the hospital and as part of the evolution of the COVID-19 pandemic, children of all ages were reincorporated into the usual scholarly and social activities. At our hospital and in Bogota (11) similar to what has been described in other publications "new" behavior increased progressively emergency consults and hospitalizations related to respiratory diseases, including pneumonia, especially those caused by syncytial respiratory virus, rhinovirus, metapneumovirus, and a lesser degree SARS-CoV-2 (12). Although penicillin was the rst-line therapy in most cases when co-infection was suspected, some cases, especially during January and February, were associated with pneumococcal co-infection, complicated pneumonia, and some of them by resistant strains, as previously reported in Bogota.…”
Section: Resultssupporting
confidence: 74%